Trans and postoperative complications associated with bichectomy surgery in clinical practice (Research, Society and Development, 2022)
Bichectomy surgery consists of removing part of the buccal fat pad located in the cheek region. This procedure has taken a large proportion among professionals in the health area, mainly in dentistry, becoming popular among the female public, where it can be indicated for aesthetic and functional purposes. However, like most surgeries, bichectomy is also capable of exposing trans and postoperative complications. Given this, this study has the main objective of explaining the probable complications associated with bichectomy. The present study was carried out through a narrative literature review based on articles searched in SciELO, Portal BVS, Google Scholar and PubMed. The articles were selected by year of publication, title, abstract and duplication and, finally, all articles were chosen for full reading and production of the present study. 21 selected articles were obtained from the initial search of 248 articles, in which reports obtained from the selected studies clarify that the most complex complications of bichectomy are Stenon's duct injury, facial nerve section, presence of infection, as well as the presence of hematoma and edema can often occur. Therefore, factors such as correct patient selection, use of imaging tests, correct use of surgical techniques and correct surgical indication, collaborate to achieve assertive results.